THE EFFECT OF BOARD SIZE, BOARD INDEPENDENCE, AND THE COMPOSITION OF BOARD INDEPENDENCE ON ACCRUAL AND REAL EARNINGS MANAGEMENT - Fitrasari, Rizkia (UI Scholars Hub, 2023)
This paper examines the effect of board size, board independence, and the composition of board independence on mitigating accrual and real earnings management by using a sample from companies listed in the S&P 500 index from 2010 to 2019. The study uses random-effect regression analysis and finds evidence that large board size is an ineffective tool for reducing earnings management. In contrast, larger board independence proves to mitigate earnings manipulation. However, when board size interacts with board independence, the result becomes more positive indicating that board independence strengthens the positive effect of board size on earnings management. It can be suggested that a small board with small independent directors is more effective in reducing both accrual and real earnings management than a larger board with larger outside directors. The findings conclude that board characteristics are not separate individuals but complementary characters. Hence, companies should not only rely on the board's quantity but also pay attention to its quality to develop an effective board to reduce earnings management.